FROM PLANTATION PRODUCTS TRANSPORTATION TO HUMAN TRANSPORTATION: THE HISTORY OF HIGH SPEED RAILWAY IN DUTCH EAST INDIES 1929 - 1942 - Mohtar, Omar (Kementerian Pendidikan dan Kebudayaan, 2021)
The train that appeared in Dutch East Indies in the mid 19th century was originally used for plantation product transport. However, the train was also used as transportation for the public. In 1894, between Batavia and Surabaya was connected with the railway line. Both cities can be reached by train in two days. To reduce travel time between those two cities, the Dutch East Indies railway company, Staatsspoorwegen was launched two high-speed trains, Eendaagsche Express in 1929 and Java Nacht Express in 1936. These two high-speed trains brought changes for railways condition in Dutch East Indies, especially in Java. During operation, these two high-speed trains also had interesting stories to write about. To write this problem, historical methods are used which consisting of heuristics, criticism, interpretation, and historiography. Based on the research conducted, these two high-speed trains made the travel time of Batavia – Surabaya 12 hours and made railways technology in the Dutch East Indies develop.